If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -6(x + 1) = 2 + -5x Reorder the terms: -6(1 + x) = 2 + -5x (1 * -6 + x * -6) = 2 + -5x (-6 + -6x) = 2 + -5x Solving -6 + -6x = 2 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -6 + -6x + 5x = 2 + -5x + 5x Combine like terms: -6x + 5x = -1x -6 + -1x = 2 + -5x + 5x Combine like terms: -5x + 5x = 0 -6 + -1x = 2 + 0 -6 + -1x = 2 Add '6' to each side of the equation. -6 + 6 + -1x = 2 + 6 Combine like terms: -6 + 6 = 0 0 + -1x = 2 + 6 -1x = 2 + 6 Combine like terms: 2 + 6 = 8 -1x = 8 Divide each side by '-1'. x = -8 Simplifying x = -8
| 6(4y+1)-1=5(6y+3)-19 | | 7(3y+4)=21 | | -16x^2+112x+100=0 | | X^2+x-12y^2=0 | | (4.1/x)=(3/9) | | 2(4c+1)=7(c+1) | | x+[x(9.7)]=72.40 | | 3z-8=5z-3z | | 2(4x+1)=7(c+1) | | 2x^2+47x-198=0 | | x(x+7)=24 | | 2.5=(x-4)/4 | | (27)2/3 | | (27)2/3x(81)1/4 | | 5=9/.4-r/.3 | | (7+w)(5w-1)=0 | | (x-1)(x+1)=80 | | (x-1)x(x+1)=80 | | -5.5x^2+275x-139=1906 | | 3x/.+9/.5=12 | | 2x+46=4x+10 | | 14+4(2c-1)= | | (14x/a^2)(2a^3x/7x^4) | | 3z^2+16z+13=0 | | 0.75(2m-10)=0.66m+10 | | (x+8)*8=49 | | 55-(3x+8)=3(x+4)+x | | 9f^2-26f=0 | | w^2+31w=0 | | .32=ln(y) | | 3f^2-32f-11=0 | | tanx=-1/sqrt3 |